Skin reactions to allergens from processionary caterpillars (genus Thaumetopoea) - Georgi Nikolov; Yana Kandova; Bogdan Petrunov; Plamen Mirchev; Georgi Georgiev (Problems of Infectious and Parasitic Diseases, 2020)
Background: Moths of the genus Thaumetopoea are widespread pests in the coniferous and deciduous forests in Bulgaria. Contact with the caterpillars, larval form of different Thaumetopoea species, causes a series of complaints in humans: mainly contact dermatitis (erucism), but also IgE-mediated allergic reactions.